2018
DOI: 10.4081/jlimnol.2018.1717
|View full text |Cite
|
Sign up to set email alerts
|

Variation of stream metabolism along a tropical environmental gradient

Abstract: Stream metabolism is affected by both natural and human-induced processes. While metabolism has multiple implications for ecological processes, relatively little is known about how metabolic rates are influenced by land use in tropical streams. In this study, we assessed the metabolic characteristics and related environmental factors of six streams located in a transition area from Cerrado to Atlantic Forest (São Carlos/Brazil). Three streams were relatively preserved, while three were flowing through more agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 69 publications
3
14
1
8
Order By: Relevance
“…Above a molar Redfield ratio of N:P of 16:1 [62], P is expected to limit algal growth (N is in excess), and below this ratio there is an N deficit (P is in excess). The authors of [58] presented molar TN:TP ratios of 44 to 195 in the stream water for the same reaches we studied here, which would suggest P limitation. The lack of a relationship between SRP uptake metrics and DIN concentrations further supports P limitation as the increased availability of N should not facilitate SRP uptake if phosphorus is the primary limiting nutrient.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Above a molar Redfield ratio of N:P of 16:1 [62], P is expected to limit algal growth (N is in excess), and below this ratio there is an N deficit (P is in excess). The authors of [58] presented molar TN:TP ratios of 44 to 195 in the stream water for the same reaches we studied here, which would suggest P limitation. The lack of a relationship between SRP uptake metrics and DIN concentrations further supports P limitation as the increased availability of N should not facilitate SRP uptake if phosphorus is the primary limiting nutrient.…”
Section: Discussionsupporting
confidence: 50%
“…Forested heterotrophic headwater streams, such as the streams we studied [58], typically have a considerable nutrient retention capacity (i.e., short S w-amb and high U amb and V f-amb [10,14]). Several studies have also reported substantial NO 3 -N, NH 4 -N, and SRP retention in pristine tropical headwater streams [40,41,57,59].…”
Section: Discussionmentioning
confidence: 99%
“…In our study reach, the relatively high NO 3 − background concentration (approximately 300 μg L −1 ) can thus be a result of the nitrification process and loading from the broader watershed. In addition, the dissolved oxygen concentrations in the studied stream (usually between 5.5 and 7.5 mg L −1 , Saltarelli et al, 2018) probably favoured the nitrification process. Ribot et al (2013) found that nitrification in a high-N stream (mean ambient NO 3 − + NH 4 + concentration of approximately 800 μg L −1 ) was lower (0.2%) than in a low-N stream (mean ambient NO 3 − + NH 4 + concentration of approximately 200 μg L −1 ; 0.2-7.6%).…”
Section: Discussionmentioning
confidence: 96%
“…Particularly, the lack of differences in canopy cover between the studied stream types probably influenced our results, because canopy cover significantly drives metabolic rates (Bunn, Davies, & Mosisch, ). We also speculate that higher ER rates in the low‐intensity agricultural sites result from higher channel complexity and potential differences in the composition and abundance of benthic biofilms (e.g., algae, bacteria, and fungi) (Saltarelli et al, ), although we did not include biofilm characteristics in this study. Also, herbicides and siltation can be important issues in agricultural streams as turbidity can absorb light and sediments can scour algae, as highlighted in other studies (e.g., see Wantzen & Mol, ).…”
Section: Discussionmentioning
confidence: 99%
“…The streams were typical meandering channels with alternating runs and pools. Benthic chlorophyll‐a is usually not greater than ~35 mg m −2 (Saltarelli et al, ). Four other sites are located in the State of Minas Gerais, in the Campo das Vertentes region (municipalities of São João del‐Rei, Tiradentes, Prados, and Resende Costa), in the Cerrado/Atlantic Rainforest transition.…”
Section: Methodsmentioning
confidence: 99%